STAGES OF INTRODUCING FUTURE TEACHERS TO INTELLECTUAL ACTIVITY ON THE BASIS OF INTELLECTUALIZED EDUCATION - Makhamatova Feruza Safaraliyevna (Galaxy International Interdisciplinary Research Journal, 2022)
Preparing future teachers for intellectual activity is one of the urgent issues of today. It is the need of the hour to develop improved stages of the process of introducing future teachers to intellectual activity.